“Aplicación de hidroabsorvente de potasio al suelo y su efecto en el volumen y la frecuencia de riego, en el cultivo de cebolla china (allium fistulosum L.) en Lamas-San Martín” - Armas Pisco, Kerlin (2009)
The objectives of the present investigation work were to evaluate the effects three dose of hydro absorbents of potassium with three watering frequency looking far to improve the growth, development, yield, quality and profitability, of the cultivation of Allium fistolosum L, in the County of you Lick Regían San Martín. The investigation work, was carríed out in the 1 am founded horticultura! the "I PACIFY", property of the Engineer Jorge Luís Peláez Rivera, sector Santa Mónica, district and county of you Lick, department and regían of San Martín, South Latítude 06°20'15", Longitude West 76°30' 45" and Altitude 835 m.s.n.m. it was driven under the experimental design it was DBCA with factorial arrangement of 4 X 4, the factor 1 gel of hydro absorbent of potassium wíth four levels O, 2, 4 and 6 g/m2 and factor F2 watering frequency with four levels O, 2, 4 and 6 days. The evaluated parameters were: volume of water and watering frequency, % of buds, plant Height, % of humidity, analysis economic weight in the production the results were subjected to a varíance analysis and it preves of stockings LSD ar DUNCAN. The consumption of water was bigger in the factor F2 with 2 g/m2 of hydro absorbent of potassium (720.27m3/ha), with the highest retention of humidity (53,41%) that allowed bigger percentage it sprouts (95,78%), the biggest height of leaf acicular (35,86 cm) and bigger yield (25,32 Tm/ha), duration after the crop far the commercialization (2 days). The levels N2, N3, N4 with 2, 4 and 6 g/m2 of hydro absorbent of potassium, applied to the floor showed better growth and development of the Onion China (Allium fistolosum), shortening the vegetative period of 39 days in comparison to the level N 1 that was harvested to the 45 days. In the factor watering frequency versus dose of hydro absorbent of potassium was not significant statistical difference. The cultivation of the Chinese onion with the yield of 25326,7 kg/ha had bigger economic profitability of 37990.05 suns.